Functional MRGPRX2 expression on peripheral blood-derived human mast cells increases at low seeding density and is suppressed by interleukin-9 and fetal bovine serum - Ieven, Toon; Goossens, Janne; Roosens, Willem; Jonckheere, Anne-Charlotte; Cremer, Jonathan; Dilissen, Ellen; Persoons, Rune; Dupont, Lieven; Schrijvers, Rik; Vandenberghe, Peter; Breynaert, Christine; Bullens, Dominique M. A. (Frontiers in Immunology, 2024)
Primary human mast cells (MC) obtained through culturing of blood-derived MC progenitors are the preferred model for the ex vivo study of MRGPRX2- vs. IgE-mediated MC activation. In order to assess the impact of culture conditions on functional MRGPRX2 expression, we cultured CD34+-enriched PBMC from peripheral whole blood (PB) and buffy coat (BC) samples in MethoCult medium containing stem cell factor (SCF) and interleukin (IL)-3, modified through variations in seeding density and adding or withholding IL-6, IL-9 and fetal bovine serum (FBS). Functional expression of MRGPRX2 was assessed after 4 weeks via flow cytometry. We found similar proportions of CD34+ MC-committed progenitors in BC and PB. Higher seeding densities (≥ 1x105 cells/mL) and exposure to IL-9 and FBS suppressed functional MRGPRX2 expression at 4 weeks, while leaving MC yield largely unaffected. IL-6 had no impact on MRGPRX2 expression. MRGPRX2-expressing MC upregulated CD63 upon stimulation with polyclonal anti-IgE, substance P and compound 48/80 at 4 weeks. Ketotifen and dasatinib but not cromolyn sodium inhibited both IgE- and MRGPRX2-dependent pathways. Our results confirm the feasibility of functional MC activation studies on PB-derived MC after a short 4-week culture and highlight the impact of culture conditions on functional MRGPRX2 expression.